Functionalised Biferrocene Systems towards Molecular Electronics - Wilson,LE; Hassenrueck,C; Winter,RF; White,AJP; Albrecht,T; Long,NJ (European Journal of Inorganic Chemistry, 2016)
Biferrocene systems offer a motif that incorporates multiple redox-active centres, enabling redox control, high levels of stability and near perfect conductance levels, and thus is an ideal participant within future molecular electronic systems. However, the incorporation of biferrocene can be restricted by current synthetic routes. Herein, we discuss a new method for the synthesis and incorporation of biferrocenyl motifs within extended conjugated systems. We have synthesised a family of compounds featuring biferrocenyl–ethynyl units with various pendant heteroaromatic linkages. The new compounds are probed with use of cyclic voltammetry, UV/Vis/near-infrared (NIR) spectroelectrochemistry and X-ray crystallography to gain further understanding of their structural and electronic properties.